MiR-154-5p Functions as an Important Regulator of Angiotensin II-Mediated Heart Remodeling. (12th September 2019) - Wang, Que; Yu, Xiaoxue; Dou, Lin; Huang, Xiuqing; Zhu, Kaiyi; Guo, Jun; Yan, Mingjing; Wang, Siming; Man, Yong; Tang, Weiqing; Shen, Tao; Li, Jian
Abstract : Chronic hypertension, valvular heart disease, and heart infarction cause cardiac remodeling and potentially lead to a series of pathological and structural changes in the left ventricular myocardium and a progressive decrease in heart function. Angiotensin II (AngII) plays a key role in the onset and development of cardiac remodeling. Many microRNAs (miRNAs), including miR-154-5p, may be involved in the development of cardiac remolding, but the underlying molecular mechanisms remain unclear. We aimed to characterize the function of miR-154-5p and reveal its mechanisms in cardiac remodeling induced by AngII. First, angiotensin II led to concurrent increases in miR-154-5p expression and cardiac remodeling in adult C57BL/6J mice. Second, overexpression of miR-154-5p to a level similar to that induced by AngII was sufficient to trigger cardiomyocyte hypertrophy and apoptosis, which is associated with profound activation of oxidative stress and inflammation. Treatment with a miR-154-5p inhibitor noticeably reversed these changes. Third, miR-154-5p directly inhibited arylsulfatase B (Arsb) expression by interacting with its 3 ′ -UTR and promoted cardiomyocyte hypertrophy and apoptosis. Lastly, the angiotensin type 1 receptor blocker telmisartan attenuated AngII-induced cardiac hypertrophy, apoptosis, and fibrosis by blocking the increase in miR-154-5p expression. Moreover, upon miR-154-5p overexpression in isolated cardiomyocytes, the protective effect of telmisartan was partially abolished. Based on these results, increased cardiac miR-154-5p expression is both necessary and sufficient for AngII-induced cardiomyocyte hypertrophy and apoptosis, suggesting that the upregulation of miR-154-5p may be a crucial pathological factor and a potential therapeutic target for cardiac remodeling.